2017
DOI: 10.1007/s12253-017-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Stain-free Histopathology of Basal Cell Carcinoma by Dual Vibration Resonance Frequency CARS Microscopy

Abstract: Basal cell carcinoma (BCC) is the most common malignancy in Caucasians. Nonlinear microscopy has been previously utilized for the imaging of BCC, but the captured images do not correlate with H&E staining. Recently, Freudiger et al. introduced a novel method to visualize tissue morphology analogous to H&E staining, using coherent anti-Stokes Raman scattering (CARS) technique. In our present work, we introduce a novel algorithm to post-process images obtained from dual vibration resonance frequency (DVRF) CARS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…Same group demonstrated that integration of multiple multiphoton modalities can be highly productive in recognizing advanced carcinoma of hypopharynx, larynx, and the left tonsil in a clinical case study and has the potential to replace conventional H&E staining [48] . Wikonkal and co‐workers introduced algorithm based on dual vibration resonance frequency (DVRF)‐CARS measurements to reproduce high quality pseudo H&E images of basal cell carcinoma (BCC) samples [49] …”
Section: Coherent Raman Scatteringmentioning
confidence: 99%
“…Same group demonstrated that integration of multiple multiphoton modalities can be highly productive in recognizing advanced carcinoma of hypopharynx, larynx, and the left tonsil in a clinical case study and has the potential to replace conventional H&E staining [48] . Wikonkal and co‐workers introduced algorithm based on dual vibration resonance frequency (DVRF)‐CARS measurements to reproduce high quality pseudo H&E images of basal cell carcinoma (BCC) samples [49] …”
Section: Coherent Raman Scatteringmentioning
confidence: 99%
“…Using photonic crystal fiber-based CARS microscopy, the capability of multimodal imaging was demonstrated by an alternative femtosecond system to study lesion development in myocardial infarction-prone, hyperlipidemic rabbits [70]. Moreover, CARS has been used to skin biopsy [17,[71][72][73][74] and for stain-free histopathology. An imaging platform based on broadband coherent anti-Stokes Raman scattering (BCARS) FIGURE 4 | (A) Adipocyte cellular lipid disintegration induced by forskolin [55].…”
Section: Tissue Imagingmentioning
confidence: 99%
“…Kutatócsoportunk kísérletei során BCC és kontroll bőrmintákban vizsgálta különböző kvantitatív analízis módszerekkel a kollagénrostok tulajdonságait BCC detektálása érdekében (1). CARS technika alkalmazásával speciális képalkotási beállítások mellett a hagyományos hematoxilin-eozin festett szövettani metszetekhez hasonló képalkotás is megvalósítható (41). A kapott képek értékelése így nem igényel külön jártasságot, így a szövettani feldolgozás egy további in vivo alternatíváját jelentheti ez a technika a jövőben.…”
Section: Nemlineáris Optikai Mikroszkópiaunclassified